Pengaruh Laba Kotor, Laba Operasi, dan Laba Bersih terhadap Perubahan Arus Kas: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Zaman, Muhammad Bintang Badrus; AC, Ali Mauludi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to provide empirical evidence regarding the effect of gross profit, operating profit, and net profit on changes in cash flow by examining each variable. This type of research is associative research with a quantitative approach method. The population in this study are companies listed on the Bursa Efek Indonesia in 2019-2021. The sample in this study was collected based on the purposive sampling technique, totaling 295 companies. The data source comes from www.idx.co.id. Data analysis technique using multiple linear regression. The results of this study are: (1) Gross profit partially has a significant effect on changes in cash flows in companies listed on the Bursa Efek Indonesia seen from the t-Statistic value -3.378030 with a Prob value. 0.0009 <0.05, (2) Operating profit partially has a significant effect on changes in cash flows in companies listed on the Bursa Efek Indondesia seen from the t-Statistic value of 3.673210 with a Prob value. 0.0003 <0.05, (3) Net profit partially has a significant effect on changes in cash flows in companies listed on the Bursa Efek Indonesia seen from the t-Statistic value of 2.349851 with a Prob value. 0.0197 < 0.05, (4) Simultaneously, gross profit, operating profit, and net profit have a significant effect on changes in cash flows in companies listed on the Bursa Efek Indonesia seen from the value of the F-statistic 9.830041 with the value of Prob(F-statistic ) 0.000000 < 0.05. Through the description that has been mentioned, it can be concluded that gross profit, operating profit, and net profit partially each have a significant effect on changes in the company's cash flow, and simultaneously gross profit, operating profit, and net profit have a significant effect on changes in cash flow company. Keywords: Gross Profit, Operating Profit, Net Profit, Changes in Cash Flow.